Selected Rheological Properties of RS3/4 Type Resistant Starch - Kapelko-Żeberska Małgorzata; Zięba Tomasz; Spychaj Radosław; Gryszkin Artur (Polish Journal of Food and Nutrition Sciences)
This study was aimed at determining the effect of acetylation degree and crosslinking of retrograded starch with adipic acid on selected rheological properties of prepared pastes and gels. The esterification of retrograded starch allowed obtaining preparations with various degrees of substitution with residues of acetic (0.7–11.2 g/100 g) and adipic acids (0.1–0.3 g/100 g). Acetylation and crosslinking caused a decrease in amylose content of the preparations (3–21 g/100 g). Solubility of the preparations in water, in a wide range of variability, was increasing along with an increasing degree of acetylation and with a decreasing degree of crosslinking (19–100 g/100 g). Values of most of the rheological coefficients determined based on the flow curves of the prepared pastes and mechanical spectra of gels (3.5<K<31.5 Pa×sn, 4.2<τ0C<70 Pa, 0.26<tg α<0.57) were increasing in a wide range along with increasing crosslinking of starch. Changes in the rheological properties upon the effect of double modification were not the sum of changes proceeding as a result of single modifications. Instead, interaction of both factors was observed. The conducted modifications enable modelling the properties of produced preparations.